2021
DOI: 10.1038/s41467-021-27146-2
|View full text |Cite
|
Sign up to set email alerts
|

Structural and functional analysis of the promiscuous AcrB and AdeB efflux pumps suggests different drug binding mechanisms

Abstract: Upon antibiotic stress Gram-negative pathogens deploy resistance-nodulation-cell division-type tripartite efflux pumps. These include a H+/drug antiporter module that recognizes structurally diverse substances, including antibiotics. Here, we show the 3.5 Å structure of subunit AdeB from the Acinetobacter baumannii AdeABC efflux pump solved by single-particle cryo-electron microscopy. The AdeB trimer adopts mainly a resting state with all protomers in a conformation devoid of transport channels or antibiotic b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
68
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(73 citation statements)
references
References 70 publications
3
68
0
Order By: Relevance
“…The identified pumps belong to the Resistance Nodulation cell Division (RND) protein superfamily, one of the most studied antiporters found in bacteria [ 57 ]. The identified genes were highly similar to acr B , encoding a multidrug efflux pump [ 58 ]. Acr B is a well-described antiporter involved in resistance to lipophilic β-lactam antibiotics, such as carbapenems and cephalosporins, fluoroquinolones, tetracyclines (including tigecycline), chloramphenicol, macrolides, trimethoprim, ethidium, rifampicin, and novobiocin [ 58 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The identified pumps belong to the Resistance Nodulation cell Division (RND) protein superfamily, one of the most studied antiporters found in bacteria [ 57 ]. The identified genes were highly similar to acr B , encoding a multidrug efflux pump [ 58 ]. Acr B is a well-described antiporter involved in resistance to lipophilic β-lactam antibiotics, such as carbapenems and cephalosporins, fluoroquinolones, tetracyclines (including tigecycline), chloramphenicol, macrolides, trimethoprim, ethidium, rifampicin, and novobiocin [ 58 ].…”
Section: Resultsmentioning
confidence: 99%
“…The identified genes were highly similar to acr B , encoding a multidrug efflux pump [ 58 ]. Acr B is a well-described antiporter involved in resistance to lipophilic β-lactam antibiotics, such as carbapenems and cephalosporins, fluoroquinolones, tetracyclines (including tigecycline), chloramphenicol, macrolides, trimethoprim, ethidium, rifampicin, and novobiocin [ 58 ]. It is of particular interest as previous studies showed that A. butzleri strains exhibited resistance to a variety of antibiotics, where the majority of them belong to β-lactams and some to quinolones and coumarins [ 15 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Looking at all cluster representatives, we identified three main binding modes. The first binding mode (BM1) is located in the groove, where the central aromatic core is 3 Heat map of contacts (%) between all poses of LFX with the DP T of AcrB -Contacts within 3.5 Å found in the experimental structure (PDB Id: 7B8T 32 ) are reported in red boldface involved in a p-p stacking interaction with F178, F615 and F628, the carboxyl group faces K151 and the 7-piperazyl ring points towards the HT (Fig. 6C).…”
Section: Systematic Application To Fqsmentioning
confidence: 99%
“…Gly288 is a distal binding pocket residue ( Fig. 1b ), close to the hydrophobic pit, where multiple drugs bind in the binding monomer ( 13 , 22 , 28 33 ). Results are shown in Table 1 .…”
Section: Introductionmentioning
confidence: 99%